Synthesis and Evaluation of a Fluorine-18 Radioligand for Imaging Huntingtin Aggregates by Positron Emission Tomographic Imaging - Kaur, Tanpreet; Brooks, Allen F.; Lapsys, Alex; Desmond, Timothy J.; Stauff, Jenelle; Arteaga, Janna; Winton, Wade P.; Scott, Peter J. H. (Frontiers in Neuroscience, 2021)
Mutations in the huntingtin gene (HTT) triggers aggregation of huntingtin protein (mHTT), which is the hallmark pathology of neurodegenerative Huntington’s disease (HD). Development of a high affinity 18F radiotracer would enable the study of Huntington’s disease pathology using a non-invasive imaging modality, positron emission tomography (PET) imaging. Herein, we report the first synthesis of fluorine-18 imaging agent, 6-(5-((5-(2,2-difluoro-2-(fluoro-18F)ethoxy)pyridin-2-yl)methoxy)benzo[d]oxazol-2-yl)-2-methylpyridazin-3(2H)-one ([18F]1), a radioligand for HD and its preclinical evaluation in vitro (autoradiography of post-mortem HD brains) and in vivo (rodent and non-human primate brain PET). [18F]1 was synthesized in a 4.1% RCY (decay corrected) and in an average molar activity of 16.5 ± 12.5 GBq/µmol (445 ± 339 Ci/mmol). [18F]1 penetrated the blood-brain barrier of both rodents and primates, and specific saturable binding in post-mortem brain slices was observed that correlated to mHTT aggregates identified by immunohistochemistry.